Investigation of chemical ageing and its effect on static and fatigue strength of continuous fibre reinforced plastics. (November 2016) - Flore, D.; Wegener, K.; Seel, D.; Oetting, C.C.; Bublat, T.
Abstract: The long term durability of continuous glass fibre reinforced thermosets with epoxy resin at high temperature and an oxygen-environment is investigated in detail. An extensive ageing-study is performed to detect the ageing effects on the residual strength in different laminate layups and to identify the corresponding damage mechanisms. Thermal degradation is found to be the dominant damage mechanism and the weight loss is found to be the most suitable measure of damage. A new phenomenological model that is based on the time-temperature-superposition principle and a master-relation between the residual strength and weight loss is presented to model the ageing effect on the residual strength. Fatigue experiments of pre-aged specimen are performed to verify the ageing effects on the fatigue strength. A simple methodology predicting the fatigue life of pre-aged specimen from the residual static strength is demonstrated and validated experimentally for several layups.